«Schreiben ist wie küssen, nur ohne Lippen». Die virtuelle Liebe in “Gut gegen Nordwind” (2006) von Daniel Glattauer: [«Writing is like kissing, only without lips». Virtual love in “Gut gegen Nordwind” (2006) by Daniel Glattauer] (Studia austriaca, 2021)
Daniel Glattauer’s novel Gut gegen Nordwind (2006), English translation: Love virtually (2011) is the first email-novel of German literature. The love triangle between Leo Leike, Emma and Bernhard Rothner is narrated through 785 emails. Their “computer mediated communication” gives birth to a virtual world that is separated from their ordinary lives. This virtual dimension becomes the projection screen for their identities, bodily representations and desires. It also becomes their cage as they will never meet in reality.